Improved Chondrotoxic Profile of Liposomal Bupivacaine Compared With Standard Bupivacaine After Intra-articular Infiltration in a Porcine Model. Issue 1 (January 2018) - Shaw, K. Aaron; Moreland, Colleen; Jacobs, Jeremy; Hire, Justin M.; Topolski, Richard; Hoyt, Nathan; Parada, Stephen A.; Cameron, Craig D.
Background: Increasingly, liposomal bupivacaine is being used with multimodal pain management strategies. In vitro investigations have shown decreased chondrotoxicity profiles for liposomal bupivacaine; however, there is no evidence regarding its in vivo effects. Hypothesis/Purpose: This study sought to investigate the in vivo chondrotoxicity of liposomal bupivacaine, hypothesizing that there would be increased chondrocyte viability after exposure to liposomal bupivacaine when compared with standard bupivacaine. Study Design: Controlled laboratory study. Methods: Eight juvenile, female Yorkshire cross piglets underwent a lateral stifle joint injection with either 1.3% liposomal bupivacaine or 0.5% bupivacaine. Injections were performed on one joint per animal with no injection to the contralateral knee, which served as the control. Chondrocyte viability was assessed 1 week after injection with a live-dead staining protocol and histologic examination. Results: Significant chondrocyte death was seen with the live-dead staining in the bupivacaine group (33% nonviable cells) in comparison with liposomal bupivacaine (6.2%) and control (5.8%) groups ( P < .01). However, histologic examination showed no differences in chondral surface integrity, fibrillation, and chondrocyte viability. Conclusion: Liposomal bupivacaine was found to be safe for intra-articular injection in this animal model. Although bupivacaine demonstrated decreased chondrocyte viability on a cellular level, histologically there were no changes. This study highlights the dichotomy between fluorescent staining and histologic appearance of articular chondrocytes in short-term analyses of viability. Clinical Relevance: This study supports the peri-articular application of liposomal bupivacaine in the setting of preserved articular cartilage. A single injection of standard bupivacaine did not produce histologic changes in the articular cartilage.